Measuring cohesive energy of van der Waals heterostructures by nanoparticle intercalation method. (March 2022) - Lou, Liqun; Chen, Peijian; Xiang, Chunping; Peng, Juan; Zhang, Shuwen
Abstract: To assemble new heterojunctions and fulfill promising applications of two-dimensional materials, it is crucial to understand the interfaces properties of various heterostructures. Significant challenges exist in accurately measuring cohesive energies of van der Waals heterostructures, largely due to the difficulty and complexity in proceeding testing methods such as peeling, nanoindentation, etc. Herein, we propose a facile and effective method, i.e., nanoparticle intercalation method to accurately evaluate cohesive energy of heterostructures through theoretical analysis and molecular dynamics simulation. It is found that the shape of nanoparticles has negligible impact on the measured cohesive energy. The nanoparticle measurement method with multiple nanoparticles can be well employed to obtain the cohesive energy in a single test. The results should be helpful for the experimental design of van der Waals heterostructures in a wide range of applications, including tunneling transistors, flexible electronics, as well as photovoltaic devices. Highlights: The nanoparticle intercalation measurement method can be effectively utilized to evaluate the cohesive energy of vdw heterostructures. The effect of various geometric and material parameters on the accurate measurement is uncovered. The method with multiple nanoparticles can be well employed to obtain the cohesive energy in a single test.